Tree species distribution in temperate forests is more influenced by soil than by climate. Issue 22 (11th October 2017) - Walthert, Lorenz; Meier, Eliane Seraina
Abstract: Knowledge of the ecological requirements determining tree species distributions is a precondition for sustainable forest management. At present, the abiotic requirements and the relative importance of the different abiotic factors are still unclear for many temperate tree species. We therefore investigated the relative importance of climatic and edaphic factors for the abundance of 12 temperate tree species along environmental gradients. Our investigations are based on data from 1, 075 forest stands across Switzerland including the cold‐induced tree line of all studied species and the drought‐induced range boundaries of several species. Four climatic and four edaphic predictors represented the important growth factors temperature, water supply, nutrient availability, and soil aeration. The climatic predictors were derived from the meteorological network of MeteoSwiss, and the edaphic predictors were available from soil profiles. Species cover abundances were recorded in field surveys. The explanatory power of the predictors was assessed by variation partitioning analyses with generalized linear models. For six of the 12 species, edaphic predictors were more important than climatic predictors in shaping species distribution. Over all species, abundances depended mainly on nutrient availability, followed by temperature, water supply, and soil aeration. The often co‐occurring species responded similar to these growth factors. Drought turned out to be a determinant of the lower range boundary for some species. We conclude that over all 12 studied tree species, soil properties were more important than climate variables in shaping tree species distribution. The inclusion of appropriate soil variables in species distribution models allowed to better explain species' ecological niches. Moreover, our study revealed that the ecological requirements of tree species assessed in local field studies and in experiments are valid at larger scales across Switzerland. Abstract : At present, the abiotic requirements and the relative importance of the different abiotic factors are still unclear for many temperate tree species. With data from more than thousand forest stands across Switzerland, we evaluated the relative importance of temperature, water, nutrients, and soil aeration for the distribution of 12 temperate tree species along environmental gradients by use of variation partitioning analyses. We found that species abundances depended mainly on nutrient availability, followed by temperature, water supply, and soil aeration. Edaphic variables were more important than climate variables in shaping species distribution.